Evaluation of total polyphenolic content and free radical scavenging activity of sucessive extracts of Amaranthus tricolor, Pimpenella tirupathansis & Amorphophallus paeoniifolius - G.THARUN GOUD; PAVAN KUMAR PINDI (International Journal of Pharma and Bio Sciences, 2017)
Plants are the basic source of knowledge of modern medicine. Almost all the parts of the plant, namely leaves, flowers, fruits, bark, roots, stem and seeds are known to have various medicinal properties. The trend of using natural products has increased and the active plant extracts are frequently screened for new drug discoveries and for the presence of antimicrobials, anticancer agents and antioxidants. Laboratories of the world have found literally thousands of phytochemicals which have inhibitory effects on all types of microorganisms in vitro. More of these compounds should be subjected to animal and human studies to determine their effectiveness in whole-organism systems, including in particular toxicity studies as well as an examination of their effects on beneficial normal microbiota. An increasing demand for natural additives has shifted the attention from synthetic to natural antioxidants. As vegetables are found to be good source of antioxidants and the present study is to examine the potential & antimicrobial activity of extracts of leaves of Amaranthus tricolor& Pimpenella tirupathansis with corns of Amorphophallus paeoniifolius. Antioxidant potential of leaves of Amaranthus tricolor, Pimpenella & corns of Amorphophallus were studied by using method like DPPH and reducing power. The aqueous extracts of Amorphophallus showed maximum scavenging activity of DPPH followed by reducing power respectively when compared with Pimpenella & Amaranthus. Total phenols were found to be 150.16 (Amaranthus); 174 (Pimpenella) and 231.39 (Amorphophallus) mg/g Gallic acid equivalent /g of dry material. These results suggest that phenolic and flavonoids in the leaves proved substantial antioxidant activity ofmaranthus tricolor, Pimpenella tirupathansis, Amorphophyllus poeniophyllus. The results obtained from phytochemical screening, antioxidant and antimicrobial analysis of Amaranthus tricolor, Pimpenella tirupathansis, Amorphophyllus paeoniifolius indicate these plants as “natural herbal sources” which can be used in pharmaceutical industry.